Mapping Women's Community Sport Participation to Inform Sport Development Initiatives: A Case Study of Row Ontario - Rich, Kyle A.; Moore, Emily; Boggs, Jeffrey; Pegoraro, Ann (Frontiers in Sports and Active Living, 2022)
Using a spatial analysis methodology, we analyzed sport participation through membership data of a Provincial Sport Organization (PSO) in Ontario, Canada. Specifically, our analysis brings attention to the participation of women and girls in Row Ontario and the urban and rural nature of the PSO's membership. This research was conducted in partnership with the PSO to provide insights into how contextual factors influence sport participation and how these findings can inform future sport development efforts. Our results demonstrate that women and girls represented the majority of participants within the PSO and highlight an opportunity to use participant centered approaches for sport development to grow women and girls' participation. This is a promising outcome as women and girls are generally underrepresented in sport and may face greater participation barriers in rural contexts.